2023
DOI: 10.1177/01461672231180450
|View full text |Cite
|
Sign up to set email alerts
|

In it Together: Relationship Transitions and Couple Concordance in Health and Well-Being

Abstract: Events that change the family system have the potential to impact couple dynamics such as concordance, that is, partner similarity in health and well-being. This project analyzes longitudinal data (≥ two decades) from both partners of up to 3,501 German and 1,842 Australian couples to investigate how couple concordance in life satisfaction, self-rated health, mental health, and physical health might change with transitioning to parenthood and an empty nest. Results revealed couple concordance in intercepts (av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Whereas Lee (1997) found that differentiation of self leads to higher mental wellbeing. Furthermore, differentiation of self plays a significant role in the development of couple satisfaction (Ferreira, et al, 2014), marital satisfaction (Kinga, 2014;Lim & Jennings, 1996) and spirituality (Jankowski & Vaughn, 2009); all these factors are also found to contributing factors of life satisfaction (Kasapoğlu & Yabanigül, 2018;Mincu & Taşcu, 2015;Yaden et al, 2022) and mental wellbeing (Kumar, 2015;Pauly et al, 2023;Smith-MacDonald et al, 2017;Yousefi, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Lee (1997) found that differentiation of self leads to higher mental wellbeing. Furthermore, differentiation of self plays a significant role in the development of couple satisfaction (Ferreira, et al, 2014), marital satisfaction (Kinga, 2014;Lim & Jennings, 1996) and spirituality (Jankowski & Vaughn, 2009); all these factors are also found to contributing factors of life satisfaction (Kasapoğlu & Yabanigül, 2018;Mincu & Taşcu, 2015;Yaden et al, 2022) and mental wellbeing (Kumar, 2015;Pauly et al, 2023;Smith-MacDonald et al, 2017;Yousefi, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%